Winter sports resort complexes of the «kurin» edition - Seregin, Iouri; Kovalchuk, Kseniia (КНУБА, 2014)
Holidays in the mountains became as much popular as holiday by the sea in summer thanks to alpine skiing facilities technologies and mountain slope development. The mountain skiing tourism became the lifestyle of the millions of people.
Keywords: mountain skiing tourism; mountain skiing resort (MSR); hotel in the mountains; passive house; гірськолижний туризм; гірськолижний курорт (ГКЛ) готель в горах; «пасивний будинок»; горнолыжный туризм; горнолыжный курорт (ГЛК); гостиница в горах; «пассивный дом»; 725.75"324"